Issues of E-banking transaction: An empirical investigation on Malaysian customers perception - Haque, A. K. M. Ahasanul; Ismail, Ahmad Zaki; Daraz, Abu Hayat (Asian Network for Scientific Information, 2009)
This study investigated the determinant factors of consumers' perception on E-banking transaction in Internet banking by Malaysian bank consumers. The research framework was developed to testify the statistical relationships between consumer perceptions and E-banking transaction. Factor analysis was performed to extraction and make initial decision on the number of factors underlying asset of measured variables of interest. Thereafter, multiple regression was estimated to anticipate the effects of the explanatory variables. This study showed that only secure transaction, have significant impact on consumers perception about E-banking transaction. Rest three factors regulatory framework, service quality and sufficient mechanism negligible impact and hypothesis was rejected. This study offers an insight into E-banking in Malaysia, which has not been previously been investigated and much statistical significance makes this study a potential cornerstone for future research.